Intra-household resource allocation and familial ties - Harounan Kazianga; Zaki Wahhaj (University of Kent, School of Economics, 2016)
In this paper, we investigate the link between intra-household resource allocation and familial ties between household members. We show that, within the same geographic, economic and social environments, households where members have "stronger" familial ties (e.g. a nuclear family household) achieve near Pareto efficient allocation of productive resources and Pareto efficient allocation of consumption while households with "weaker" familial ties (e.g. an extended family household) do not. We propose a theoretical model of the household based on the idea that altruism between household members vary with familial ties which generates predictions consistent with the observed empirical patterns.
Keywords: O12; D13; Q1; 330; Intra-household Allocation; Social Norms; Extended Families; Altruism; Household Farms; Income Shocks; Risk-sharing; Consumption Smoothing